Osteoporotic 3-4 part humeral proximal fractures in the elderly with ASA 3 score: comparison of surgical and non-surgical treatments - Di Francesco, Alexander; Bizzarri, Leonardo; Liaci, Enrica; Bizzarri, Francesco (Lo Scalpello - Journal, 2022)
Objectives. To compare the outcomes of non-surgical treatment and reverse shoulder arthroplasty (RSA) in osteoporotic four-part proximal humeral fracture (PHF) in elderly population with ASA 3 score to determine which interventions are the most appropriate for management. Methods. Between January 2014 and December 2016, 60 patients aged from 75 to 90 years with osteoporotic four-part PHF were enrolled and were randomly allocated to non-surgical treatment or RSA (n = 30). Clinical indexes for patients in the two groups, such as Constant-Murley score (CMS), Disability of Arm, Shoulder and Hand (DASH) score, individual subject evaluation of the outcomes and plain X-ray were compared at 36 months of follow-up.Results. CMS, DASH score, activities of daily living (ADL), and range of motion (ROM) were significantly higher in the nonoperative group than in the RSA group at the last follow-up, whereas pain was greater in the RSA group at 12 months. In addition, patients in the nonoperative group had higher abduction, external rotation with elbow (ER 1), strength and satisfactory rating compared with RSA at the last follow-up. There were 2 cases who have suffered from superficial infection and 4 cases from shoulder stiffness in the RSA group. Conclusions. Conservative treatment is a possible option in elderly patients with ASA 3 score valuation.